2007
DOI: 10.1111/j.1537-2995.2007.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis C virus infection among blood donors in Israel: a case‐control study between native Israelis and immigrants from the former Soviet Union

Abstract: Although the strength of risk factors for HCV differs between Israeli and immigrant BDs, most factors studied did not differ between the groups. Therefore, changes in screening of all BDs are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…The study also depicted an association between syphilis and other transfusion-transmitted diseases such as HIV, hepatitis B, and C, when compared to the donor population that was seronegative for syphilis, and it concurred with our previous observations of higher prevalence of hepatitis C among blood donors who immigrated to Israel from the former USSR [32]. …”
Section: Discussionsupporting
confidence: 89%
“…The study also depicted an association between syphilis and other transfusion-transmitted diseases such as HIV, hepatitis B, and C, when compared to the donor population that was seronegative for syphilis, and it concurred with our previous observations of higher prevalence of hepatitis C among blood donors who immigrated to Israel from the former USSR [32]. …”
Section: Discussionsupporting
confidence: 89%
“…A local study that was done previously had also observed a rising seroprevalence of 0.89% [17]. This finding is consistent with the increasing trend of syphilis seropositivity observed in blood donors of Israel [18]. A study done in Iran also found a rising trend of syphilis frequency in their population; however, the frequency found in this study was 0.04% [19].…”
Section: Discussionsupporting
confidence: 88%
“…Other strong risk factors among native Israelis included close contact with infected individuals and surgery. The risk factors identified in the former Soviet Union immigrants included gum surgery, hospitalization without surgery and receiving injection therapies (143). IDU was found to be a significant risk factor among 29 acute hepatitis C patients, accounting for 20.6% of infections, but a higher percentage of patients (65.5%) could have been exposed through medical procedures (145).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Multiple researchers identified immigration from the former USSR as one of the key sources of HCV infections in the country. The authors suggested that mass vaccination using non-disposable needles in the former Soviet Union and the spread of infection within families could be the cause of a higher prevalence among immigrants (143,144). The risk factors among immigrants and native Israelis were assessed in a case-control study of 434 blood donors (143).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation